PENYULUHAN DIABETES MELITUS (DM) DAN SKRINING PENYAKIT TIDAK MENULAR (GLUKOSA DARAH SEWAKTU) DI SMK BINA WARGA KABUPATEN PANDEGLANG 2022 - Ucu Wandi Somantri; Heny Sasmita (Universitas 17 Agustus 1945 Semarang, 2025)
Non-communicable diseases are non-communicable diseases such as diabetes, cholesterol and gout which are public health problems that cause death for 36 million people out of all deaths in the world. Non-Communicable Diseases can be prevented through early detection and risk control factors of Non-Communicable Diseases. Screening aims at early detection and connecting factors. The risk of non-communicable diseases including diabetes mellitus in students of SMK Bina Warga Pandeglang Regency. Non-Communicable Disease screening is carried out by taking blood vessels at the respondent's fingertips which are then tested with an autocheck device. The examination was carried out on 51 respondents who underwent the examination, consisting of 6 men and 45 women. The results of the examination obtained the respondent's blood glucose level so far (normal 42 people and height 9 people).